2019
DOI: 10.1186/s12864-019-5864-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cell-specific effects of genetic variations using tRNA microarrays

Abstract: Background By definition, effect of synonymous single-nucleotide variants (SNVs) on protein folding and function are neutral, as they alter the codon and not the encoded amino acid. Recent examples indicate tissue-specific and transfer RNA (tRNA)-dependent effects of some genetic variations arguing against neutrality of synonymous SNVs for protein biogenesis. Results We performed systematic analysis of tRNA abunandance across in various models used in cystic fibrosis (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…Development of high-throughput tools, including tRNAbased microarrays (Dittmar et al, 2004;Polte et al, 2019), and more recently, optimized methods for high-throughput tRNA sequencing (Zheng et al, 2015;Gogakos et al, 2017;Shigematsu et al, 2017;Erber et al, 2020;Pinkard et al, 2020) have provided more efficient means for detection of individual tRNA-level fluctuations and enabled the discovery of key trends that regulate cell homeostasis in a tRNAdependent way. These studies revealed that tissue-specific tRNA expression generally reflects codon preference of highly expressed genes in human, indicating the importance of translation regulation via tRNA abundance in different tissues (Dittmar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Development of high-throughput tools, including tRNAbased microarrays (Dittmar et al, 2004;Polte et al, 2019), and more recently, optimized methods for high-throughput tRNA sequencing (Zheng et al, 2015;Gogakos et al, 2017;Shigematsu et al, 2017;Erber et al, 2020;Pinkard et al, 2020) have provided more efficient means for detection of individual tRNA-level fluctuations and enabled the discovery of key trends that regulate cell homeostasis in a tRNAdependent way. These studies revealed that tissue-specific tRNA expression generally reflects codon preference of highly expressed genes in human, indicating the importance of translation regulation via tRNA abundance in different tissues (Dittmar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although synonymous site may changing the RNA secondary structure (23), we observed only one synonymous site appeared in the stem-loop regions overlapped with the ORF1ab gene in one genome (20). A tendency of mutation to rare codons shown by the negative value of log2 FCTE of the ORF1ab:A fragment (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Although such an estimation may be even more suitable for evaluation of adaptation of virus genome, because the codon usage frequency also reflects the stability of interactions between mRNA and anticodon in addition to tRNA abundance( 12), an direct measurement of tRNA abundance may help to further address various effects of translation kinetics. FCTE in the M and N genes confirm the adaptation of the genome of SARS-CoV-2 to the target tissue (12,20). Translation products of the M and N genes, both the most abundant structural proteins, interact with the genomic RNA intimately in the viral replication and virion packaging (21,22).…”
Section: Discussionmentioning
confidence: 76%
“…qRT-PCR assays displayed a linear range over five (R 2 = 0.99969, efficiency = 91%) or four (R 2 = 0.998; efficiency = 93%) orders of magnitude for CFTR or NPT, respectively. tRNA microarrays were performed as previously described (13,44). Fluorescent stem-loop RNA/DNA oligonucleotide bearing a Cy3 fluorescent dye (Microsynth) was ligated to total tRNA from CFBE41o − or FRT cells and compared to HeLa tRNA labeled with Atto647 stem-loop RNA/DNA oligonucleotide.…”
Section: Methodsmentioning
confidence: 99%